2019
DOI: 10.1002/lt.25498
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Intracardiac Thrombus During Liver Transplantation

Abstract: Intracardiac thrombus (ICT) is an intraoperative complication with high mortality that occurs during orthotopic liver transplantation (OLT). Patients with end‐stage liver disease have compromised coagulation pathways, and when combined with stressors of surgery, thrombi can form. However, it is unknown which patients are most likely to develop ICT. We performed a retrospective cohort study of all OLT patients at our hospital from 2010 to 2017 to identify risk factors for ICT. An analysis was performed with con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 18 publications
1
27
0
Order By: Relevance
“…Other reports suggest that thrombectomy and/or thrombolysis may be associated with lower rates of patient mortality; although this trend has not been shown to be statistically significant. 4 , 5 Groose et al, 11 in a single retrospective study center, reported that the odds of developing ICT were significantly lower following the administration of intravenous heparin before IVC clamping and thus concluded heparin to be protective. This would suggest that venous stasis, vascular clamping, and reperfusion could contribute to clot formation ( Video 2, SDC , http://links.lww.com/TXD/A359 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other reports suggest that thrombectomy and/or thrombolysis may be associated with lower rates of patient mortality; although this trend has not been shown to be statistically significant. 4 , 5 Groose et al, 11 in a single retrospective study center, reported that the odds of developing ICT were significantly lower following the administration of intravenous heparin before IVC clamping and thus concluded heparin to be protective. This would suggest that venous stasis, vascular clamping, and reperfusion could contribute to clot formation ( Video 2, SDC , http://links.lww.com/TXD/A359 ).…”
Section: Discussionmentioning
confidence: 99%
“…16 Patients with higher MELD scores are sicker by definition, and may be prone to more severe complications such as intraoperative thromboembolism. 17 As such, we speculate that practitioners' research priorities may reflect their local experience with this rare but catastrophic complication of transplant, but our data do not allow for us to do more than speculate.…”
Section: Discussionmentioning
confidence: 81%
“…Patients who undergo liver transplant in the Northeast, for example, are transplanted with higher Model for End‐Stage Liver Disease (MELD) scores, compared to patients in the south 16 . Patients with higher MELD scores are sicker by definition, and may be prone to more severe complications such as intraoperative thromboembolism 17 . As such, we speculate that practitioners’ research priorities may reflect their local experience with this rare but catastrophic complication of transplant, but our data do not allow for us to do more than speculate.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of ICT and/or PTE during OLT has been reported to be as low as 0.36% and as high as 6.25%. [1][2][3][4] ICT can occur at any point during liver transplantation [1,2,5] and is associated with patient factors such as Model for End-Stage Liver Disease (MELD) score, donor body mass index, and organ warm ischemia time (WIT). [4] Although rare, ICT can be a catastrophic event leading to clinically significant hemodynamic instability, intraoperative cardiac arrest (ICA), or intraoperative death (IOD) and is associated with an intraoperative mortality rate of 45%-68%.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] ICT can occur at any point during liver transplantation [1,2,5] and is associated with patient factors such as Model for End-Stage Liver Disease (MELD) score, donor body mass index, and organ warm ischemia time (WIT). [4] Although rare, ICT can be a catastrophic event leading to clinically significant hemodynamic instability, intraoperative cardiac arrest (ICA), or intraoperative death (IOD) and is associated with an intraoperative mortality rate of 45%-68%. [2,4,5] When TEE is not present to confirm diagnosis, ICT is typically suspected when sudden hemodynamic collapse occurs in the setting of increased central venous pressure and pulmonary artery pressures on a pulmonary artery catheter, suggesting PTE.…”
Section: Introductionmentioning
confidence: 99%